Critical Theory and the Classical World - Hudson, Martyn (Classical and Contemporary Social Theory Ser, 2018)
Cover -- Half Title -- Title Page -- Copyright Page -- Contents -- Acknowledgements -- Introduction: Critical theory and the classical world -- 1 Out of the ancient earth -- 2 Marx, Epicurus and the classical world -- 3 Mnemosyne: Art, memory, objects -- 4 Human: Troy -- 5 Force: Achilles -- 6 Enlightenment: Odysseus -- 7 Cosmos: The classical gods -- 8 Spirit: The classical statue -- 9 Domination: The Atreides -- References -- Index.